2016
DOI: 10.1186/s12909-016-0624-2
|View full text |Cite
|
Sign up to set email alerts
|

To be or not to be a facilitator of reflective learning for medical students? a case study of medical teachers’ perceptions of introducing a reflective writing exercise to an undergraduate curriculum

Abstract: BackgroundIntroducing reflective writing to a medical curriculum requires the acceptance and participation of teachers. The purpose of this study was to explore medical teachers’ views on the benefits of introducing a reflective writing exercise into an undergraduate medical curriculum, including their levels of satisfaction and their concerns. We also investigated effects on the teachers’ personal and professional development arising from their roles as novice facilitators.MethodsA qualitative approach was em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Reflective writing has a learning effect in the medical education and clinical setting (Liu, Jawitz, Zheng, Gusberg, & Kim, ; Sukhato et al., ; Wald, Haramati, Bachner, & Urkin, ). It has been suggested that writing was an effective reflection method for the cognitive process and resulted in favourable outcomes both theoretically and practically (Zarei, Pourghasemian, & Jalali, ).…”
Section: Discussionmentioning
confidence: 99%
“…Reflective writing has a learning effect in the medical education and clinical setting (Liu, Jawitz, Zheng, Gusberg, & Kim, ; Sukhato et al., ; Wald, Haramati, Bachner, & Urkin, ). It has been suggested that writing was an effective reflection method for the cognitive process and resulted in favourable outcomes both theoretically and practically (Zarei, Pourghasemian, & Jalali, ).…”
Section: Discussionmentioning
confidence: 99%
“…Reciprocally, I've written about realizing personal and professional growth as a medical educator within the IRW paradigm (Wald 2008, Wald 2010, an example of relationship-centered education (Rabow et al 2014). This was supported more recently with teachers reporting that the activity of facilitating reflective learning through a RW exercise for medical students enhanced personal and professional fulfillment and renewed their enthusiasm (Sukhato et al 2016 proceeded with caution given caveats about boundaries and physician disclosure within the clinical context (Morse et al 2008). Such sharing has, however, also been described as a means of fostering trust and rapport in the patientphysician relationship (Candib 1987) and I would hope within the teacher-student relationship as well.…”
Section: Further Reflections By Faculty and Studentmentioning
confidence: 99%
“…The development of critical reflective skills can reduce stress and foster wellness in medical students (Lutz et al 2013, Peterkin et al 2012. Benefits of IRW curriculum for both trainees (Borgstrom et al 2016, Wald et al 2009) and faculty have been reported (Wald 2008, Sukhato et al 2016). Our implementation of an IRW curriculum within our Family Medicine Clerkship has been described .…”
Section: Introduction -Interactive Reflective Writing In Medical Educmentioning
confidence: 99%
“…Teachers' beliefs refer to an integrated system of judgments that relate to teachers' classroom work (Peck & Herriot, 2015). They can help students to convey their experiences more explicitly (Sukhato et al, 2016; Siemens, Punnen, Wong, Kanji, 2010).…”
Section: Introductionmentioning
confidence: 99%